The Treatment of Metastatic Non-Small Cell Lung Cancer in the Elderly: An Evidence-Based Approach - Dawe, David E.; Ellis, Peter Michael (Frontiers in Oncology, 2014)
An increasing proportion of patients with advanced NSCLC are over 70 years old, raising unique challenges for treatment decision-making. While these patients are underrepresented in clinical trials, there is an emerging body of evidence associated with this group. The lesson of comprehensive geriatric assessment is that chronological age does not always correlate with physiological age and a variety of important comorbidities and geriatric syndromes can go undetected in a typical history and physical. These comorbidities and expected physiologic changes due to aging complicate decision-making around appropriate treatment. This review discusses geriatric assessment in elderly cancer patients and evaluates the current evidence for chemotherapy and targeted therapy for patients with advanced non-small cell lung cancer aged ≥70 years.